A Review on Hypertension, Vitamin D and the Role of Vitamin D in Hypertension: Vitamin D and Blood Pressure - Ahmad, Rahnuma; Akter, Fatema; Khan, Indira Sufia; Naoreen, Rifat; Hussain Sadia, Farhana; Sultana, Mahbuba; Islam, Taslima (Journal of the Medical College for Women & Hospital, 2024)
Hypertension is a global public health concern and millions are affected by it. It is multifactorial and initial therapeutic means is to bring about life style changes with consumption of healthy diet and regular exercise. However, despite such changes there are many patients who require pharmacological management. Vitamin D is a micronutrient that has multiple functions like in the regulation of calcium ion and bone metabolism in our body and one such role may be its influence in blood pressure regulation. Lower vitamin D levels may cause rise in Renin-angiotensin-aldosterone system(RAAS) and hence aggravate a rise in blood pressure. This narrative review aims to look in to the role of vitamin D in blood pressure control and the possible effect of supplementation in lowering blood pressure in hypertensive patients. The current information related to vitamin D and hypertension was gathered using online data base like PubMed, Scopus, Google search engine were used to retrieve the required research works. The keywords used to make the search included ‘Vitamin D’ , ‘Hypertension’ , ‘Cholecalciferol’ , ‘Vitamin D and blood pressure’. Vitamin D may be used as adjuvant therapy and large scale future studies are required to assess the role of this nutrient in hypertension. J Med Coll Women Hosp. 2024; 20 (2): 76-92